Media regulation strategies in parents of 4- to 16-year-old children and adolescents: a cross-sectional study - Tanja Poulain; Christof Meigen; Wieland Kiess; Mandy Vogel (BMC, 2023)
Abstract Background Since children can only control and limit their own media use to a limited extent, it is often the parents who regulate their children's media use. However, there is insufficient research on which strategies they use and on how these strategies are related to socio-demographic and behavioral parameters. Methods The parental media regulation strategies co-use, active mediation, restrictive mediation, monitoring, and technical mediation were assessed in a sample of 563 four- to 16-year-old children and adolescents from middle to high social strata participating in the German cohort study LIFE Child. We investigated cross-sectional associations with socio-demographic characteristics (age and sex of child, age of parent, and socio-economic status (SES)) and other behavioral parameters of children (media use, ownership of media devices, engagement in extracurricular activities) and their parents (media use). Results All media regulation strategies were applied frequently, with restrictive mediation occurring most frequently. Overall, parents of younger children and of boys mediated media use more frequently, while we observed no differences depending on SES. Regarding child behavior, the ownership of a smartphone and a tablet/personal computer/laptop was associated with more frequent technical restriction, while screen time and engagement in extracurricular activities was not associated with parental media regulation. In contrast, parental screen time was related to more frequent co-use and less frequent use of restrictive and technical mediation. Conclusion Parental regulation of child media use is influenced by parental attitudes and a perceived need for mediation (e.g., in younger children or children owning internet-enabled devices) rather than child behavior.